New perspectives on djulis (Chenopodium formosanum Koidz.) and its potential application in functional food - Amanda Tresiliana Mulio; Chien-Shan Chiu; Yung-Jia Chan; Wen-Chien Lu; Po-Hsien Li (Food Chemistry: X)
Djulis (Chenopodium formosanum Koidz.) is an endemic cereal plant to Taiwan that has been cultivated by Taiwanese aborigines for hundreds of years. Djulis Djulis is a well-known ruby cereal because it contains betanin and exhibits strong antioxidant activity. This review summarizes comprehensive information regarding proximate composition, phytochemical compounds, biological activities, and recent industrial applications. Djulis is rich in phytochemical compounds including flavonoids, phenolics, and betanin. Further assessment of cell and animal studies showed that djulis leaf, whole grain, hull, and seed extracts exhibited antioxidant, anti-aging, anti-diabetic, anticancer, anti-adipogenesis, hepatoprotective, anti-inflammatory, and gastric protective properties. Products incorporating djulis were also included in this review. This review provides new insights into the application of djulis in the development of new products.